Comparison of calcium levels in patients with benign paroxysmal positional vertigo and the other type of vertigo: Perbandingan kadar kalsium pada penderita benign paroxysmal positional vertigo dan jenis vertigo lainnya - Andi Kurnia Bintang; Marina Musyawwirina; Muhammad Iqbal Basri (Makassar Dental Journal PDGI Makassar, 2022)
Introduction: Benign paroxysmal positional vertigo (BPPV) is commonly found in older women; caused by the presence of otoconia in semicircular canals, which will stimulate the ampulla. Degeneration of otoconia and abnormal calcium metabolism could contribute to BPPV. This study aims to find a difference in serum calcium levels between idiopathic BPPV and non-BPPV vertigo patients. Methods: Cross-sectional study was held in Wahidin Sudirohusodo hospital in Makassar from August to October 2019. Subjects who fulfilled the criteria were divided into two groups (BPPV and non-BPPV). Venous blood was taken to obtain serum calcium levels. Statistical analysis was performed with SPSS software version 21. Chi-square and Mann-Whitney tests were used to determine the relationship between variables. Result: As many as 45 subjects were grouped into BPPV (n=30) and non-BPPV (n=15). Majority of subjects were female (n=30). Mean serum calcium level was significantly lower in BPPV group (8.51±0.67 vs 8.9±0.63; p=0.023). Area under curve of serum calcium level according to vertigo type was 22.4% (p<0.05). Optimal cut-off point for serum calcium level was 8.55 (p=0.024). Discussion: Majority of subjects in this study were females between 40-60 years old. Patients with BPPV tend to have lower serum calcium levels. Possible underlying me-chanisms include estrogen deficiency, otoconial degeneration, vitamin D deficiency, lack of sunlight, and abnormal calcium me-tabolism. Examination of serum calcium level and calcium supplementation could be considered for these patients. Some factors that affect serum calcium level were not considered in this study. It was concluded that examination of serum calcium level and calcium supplementation could be considered for patients with BPPV.